Hepatitis C virus mutation affects proteasomal epitope processing - Seifert, Ulrike (American Society for Clinical Investigation, 2004)
The high incidence of hepatitis C virus (HCV) persistence raises the question of how HCV interferes with host immune responses. Studying a single-source HCV outbreak, we identified an HCV mutation that impaired correct carboxyterminal cleavage of an immunodominant HLA-A2–restricted CD8 cell epitope that is frequently recognized by recovered patients. The mutation, a conservative HCV nonstructural protein 3 (NS3) tyrosine to phenylalanine substitution, was absent in 54 clones of the infectious source, but present in 15/21 (71%) HLA-A2–positive and in 11/24 (46%) HLA-A2–negative patients with chronic hepatitis C. In order to analyze whether the mutation affected the processing of the HLA-A2–restricted CD8 cell epitope, mutant and wild-type NS3 polypeptides were digested in vitro with 20S constitutive proteasomes and with immunoproteasomes. The presence of the mutation resulted in impaired carboxyterminal cleavage of the epitope. In order to analyze whether impaired epitope processing affected T cell priming in vivo, HLA-A2–transgenic mice were infected with vaccinia viruses encoding either wild-type or mutant HCV NS3. The mutant induced fewer epitope-specific, IFN-γ;–producing and fewer tetramer(+) cells than the wild type. These data demonstrate how a conservative mutation in the flanking region of an HCV epitope impairs the induction of epitope-specific CD8(+) T cells and reveal a mechanism that may contribute to viral sequence evolution in infected patients.